Pemberdayaan Masyarakat Melalui Bimbingan dan Pelatihan Pemanfaatan Legum Cover Crop Mucuna bracteata untuk Pengendalian Gulma dan Peningkatan Hara Tanah pada Perkebunan Kelapa Sawit - Veronika, Nina; Hanifah Khairiah; Antonius J Sihotang; Fatmayati Fatmayati; Nur Ama Deli (Politeknik Kampar, 2023)
Weed control in oil palm plants is very necessary because it can cause losses both directly and indirectly. Kampar Polytechnic's partner in this PKM activity is the Pancuran Gading Village Office which is the Village Government that leads the implementation of Village development, development of Village community, and empowerment of Village communities, the majority of whom are oil palm farmers. So far, oil palm farmers prefer to use herbicides to control weeds. The impact of using herbicides is that it is not environmentally friendly and tends to increase maintenance costs because the price of herbicides is increasing every year. One solution that can be used is the use of the legume cover crop (LCC) Mucuna bracteata. Apart from functioning to suppress weed growth, LCC also plays a role in increasing soil fertility. With this community service activity, it is hoped that oil palm farmers will be able to cultivate Mucuna bracteata well in order to control weeds on oil palm plantations. In this way, dependence on herbicides can be reduced and oil palm maintenance costs can become more economical.